Identification of Differentially Expressed Genes and Pathways Involved in Growth and Development of Mesona chinensis Benth Under Red- and Blue-Light Conditions - Tang, Danfeng; Huang, Qinfen; Wei, Kunhua; Yang, Xiaonan; Wei, Fan; Miao, Jianhua (Frontiers in Plant Science, 2021)
Mesona chinensis Benth (MCB) is an important Chinese herbal medicine. The plant factories might be one of the ways to solve the shortage of MCB supply. In this study, the MCB seedlings were treated under the red (R) and blue (B) lights in the plant factory. Results showed that the red light promoted the growth and development of MCB in comparison with the blue light. Under the red-light condition, the biomass, plant height, and root characteristics were significantly higher than those under blue-light condition, while the soil and plant analyzer development (SPAD) under the red-light treatment was significantly lower than that under the blue-light treatment. Red light also significantly promoted the content of soluble sugar and pectin of MCB compared with blue light. Transcriptome analysis showed that a total of 4,165 differentially expressed genes (DEGs) were detected including 2,034 upregulated and 2,131 downregulated. Of these, 1,112 DEGs including 410 upregulated and 702 downregulated genes were associated with 111 pathways. Moreover, a total of 8,723 differentially expressed transcription factors (TFs) were identified in R vs. B, and these TFs were distributed in 56 gene families. Metabonomic results revealed that a total of 184 metabolites and 99 differentially expressed metabolites (DEMs) (42 upregulated and 57 downregulated) were identified in the red- and blue-light treatments. Integrative analysis of transcriptome and metabolome unveiled that a total of 24 pathways included 70 compounds (metabolites) and were associated with 28 unigenes. In particular, these pathways included starch and sucrose metabolism, phenylpropanoid biosynthesis, cysteine and methionine metabolism, glycolysis/gluconeogenesis, and pentose and glucuronate interconversions. The unigenes included asparagine synthetase (AS), thymidine kinase (TK), alpha, alpha-trehalose-phosphate synthase (TPS), phosphatase IMPL1 (IMPL1), dihydroflavonol 4-reductase (D4R), and 4-coumarate-CoA ligase-like 6 (4CL6), bifunctional aspartokinase-homoserine dehydrogenase 1 (thrA), and abscisic acid 8′-hydroxylase 2 isoform X1 (ABA8). It was indicated that these pathways and genes might play important roles in the growth and development of MCB. This study laid a foundation for the future research of MCB.